Utilizing risk index for overdose or serious opioid-induced respiratory depression (RIOSORD) scores to prioritize offer of rescue naloxone in an outpatient veteran population: A telephone-based project. Issue 2 (3rd April 2018) - Yates, Derek; Frey, Theresa; Montgomery, Jean Charles
ABSTRACT: Background : Since 2014, the Department of Veterans Affairs (VA) has been working to address the ongoing opioid epidemic through opioid-education initiatives, the development of risk calculators, and other risk stratification tools. One primary focus of VA efforts has been the distribution of rescue naloxone kits to veterans at greatest risk of opioid-related adverse events. The purpose of this project was to identify primary care veterans at highest risk for serious opioid-related adverse events using the Risk Index for Overdose and Serious Opioid-Induced Respiratory Depression (RIOSORD) and offer rescue naloxone kits by telephone-based outreach. RIOSORD is a risk-stratification tool developed and validated within the veteran population. Methods : Veterans identified at highest risk of overdose or opioid-related adverse effects were contacted by telephone or letter to offer to provide a rescue naloxone kit between November 1 st, 2016 and February 1 st, 2017. The primary outcome of the project was the percentage of patients contacted that agreed to a naloxone prescription. Secondary outcomes included comparative efficacy of phone versus letter contact and reasons for refusal of naloxone if the offer was declined. Results : Of 41 veterans targeted by this project, most were successfully reached by telephone within three attempts (92.7%, n = 38). Approximately two-thirds of those reached by telephone agreed to a prescription for rescue naloxone (n = 26, 63.4%). The veterans that requested rescue naloxone selected the nasal formulation (n = 17) over the intramuscular auto-injector (n = 9). Conclusions : This project demonstrated that telephone-based outreach can be one method of distributing rescue naloxone to a high-risk patient population without requiring an in-person visit to a provider.